An estimation of national charcoal production: the case of Ghana. (1st March 2022) - Nketiah, K.S.; Asante, J.; Hansen, C.P.
Accurate data on the production and sources of woodfuels is necessary to ensure sustainability. National level data is scanty in most subSaharan African countries. This research aimed to provide accurate data on charcoal production in Ghana and to develop a methodology that could serve as an inspiration for future assessments, in Ghana and beyond. The study compiled data over two years from Ghana Forestry Commission's records on charcoal quantities transported on the road (Charcoal Conveyance Certificates). This data was validated by mounting sentries 24 hours daily for two weeks in 2016 and 2018, respectively, along major charcoal transport routes to capture charcoal being transported without the certificate. Charcoal production not captured through the Charcoal Conveyance Certificate and the sentries was quantified from field observation and expert panel validation. Using these three methods, the study estimated a total annual production (2018) of 1 100 000 tonnes of charcoal for Ghana. This corresponds to 15.7 million m 3 of round wood equivalent. The implications of the study findings are discussed together with the pros and cons of the methods employed.